FINANCIAL DEVELOPMENT, ENERGY CONSUMPTION AND ENVIRONMENTAL QUALITY IN DEVELOPING COUNTRIES - Akbulut, Hale (Investigación Económica, 2023)
This study aims to analyze the impact of financial development on greenhouse gas emissions in the case of developing countries, considering the spillover effects due to energy consumption. For this purpose, static and dynamic panel threshold regression models were used. The evidence obtained from the 2003-2019 period data shows that financial development has a significant threshold effect on emissions. How this effect works depends on the distinction between financial institutions and financial markets. In contrast to financial market development, in countries where the financial institution development index is above 0.356, the forces that increase emissions have been observed to weaken. DESARROLLO FINANCIERO, CONSUMO DE ENERGÍA Y CALIDAD AMBIENTAL EN PAÍSES EN DESARROLLO RESUMEN El presente estudio analiza el impacto del desarrollo financiero sobre las emisiones de gas de efecto invernadero en países en desarrollo, considerando los efectos de derrame debidos al consumo de energía. Para tal propósito, utilizamos modelos de regresión de panel dinámico con umbral. La evidencia que obtuvimos con datos para el periodo 2003-2009 muestra que el desarrollo financiero tiene un efecto de umbral significativo en las emisiones. La forma en que opera este efecto depende de la distinción entre instituciones financieras y mercados financieros. En contraste con el desarrollo del mercado financiero, se ha observado que en países donde el índice de desarrollo de las instituciones financieras es mayor que 0.356, las fuerzas que incrementan las emisiones se debilitan.